LDH and glycolytic activity as predictors of immunotherapy response in gastric cancer: a systematic review and meta-analysis - Zhu, Li; Ruan, Juanjuan; Zhang, Qing; Feng, Li; Deng, Ying; Dai, Lili; Zheng, Yuanyuan; Feng, Zhijuan; Xu, Ruihan; Liu, Keqin; Xu, Nan (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have transformed gastric cancer (GC) treatment, but response heterogeneity necessitates reliable prognostic biomarkers. This meta-analysis investigates the predictive value of metabolic (LDH, glycolytic activity) and inflammatory markers (NLR, PLR, LMR) in GC patients receiving ICIs.MethodsWe systematically analyzed 17 studies (n=3,842) from major databases through March 2024. Pooled hazard ratios (HRs) for overall survival (OS) and progression-free survival (PFS) were calculated using random-effects models, with subgroup analyses by treatment type (monotherapy/combination). Study quality was assessed via Newcastle-Ottawa Scale.ResultsElevated LDH significantly predicted poorer OS (HR=2.01, 95%CI:1.72-2.34) and PFS (HR=2.23, 95%CI:1.29-3.66), with minimal heterogeneity (I²=0%). Similarly, high NLR (HR=1.73) and PLR (HR=1.65) correlated with worse outcomes, while elevated LMR showed protection (HR=0.73). These associations remained consistent across treatment modalities and geographic regions (all Asian studies).ConclusionsLDH and inflammatory markers are robust, clinically accessible prognostic biomarkers in GC immunotherapy. Their validation enables improved risk stratification and supports development of combination strategies targeting metabolic-immune crosstalk to enhance ICI efficacy.